FINANSOWA OCENA PROJEKTU INWESTYCYJNEGO Z WYKORZYSTANIEM OPCJI RZECZYWISTYCH. STUDIUM PRZYPADKU - Mizerka, Jacek; Surma, Jacek (Wydział Prawa i Administracji UAM, 2000)
Real options are an innovative method of evaluation investments tasks. The assumption for theoretical research and trials of practical applications are the imperfections of traditional method used to the present in order to evaluate investments efforts which consisted in calculating net present value (NPV) on a basis of flows of finances. The last mentioned method does not take into consideration the responsiveness of the subjects involved with decision making process regarding changes in internal conditions and in surrounding circumstances. The theory of real options in based the theory of financial options. Through an analogy to parameters of financial options it is possible to fix up parameters of real options for the project considered. Thanks to the application of the retardation option and of extension option a new image of effectiveness of the whole task is being obtained: in both cases negative NPV result has changed into positive values - what made remunerable an investment effort treated as not remunerable up to the present and according to traditional NPV. The Authors develop their consideration on the basis of hypothetical project of constructing a hotel with restaurant resort in the vicinity of the City of Poznań.
USING REAL OPTIONS IN FINANCIAL EVALUATION OF AN INVESTMENT PROJECT. A CASE STUDY